Demographic, clinical and pathological features of sudden deaths due to myocarditis: Results from a state-wide population-based autopsy study. (March 2017) - Li, Liliang; Zhang, Yang; Burke, Allen; Xue, Aimin; Zhao, Ziqin; Fowler, David; Shen, Yiwen; Li, Ling
Highlights: Sudden deaths from myocarditis are studied over a 10-year period. Demographic, clinical and pathological features are analyzed. The incidence of fatal myocarditis is 0.70% of autopsied sudden deaths. In 17.5% cases, no significant myocyte necrosis is identified. Determination of myocarditis as cause of death remains a challenge to pathologist. Abstract: Causes of sudden cardiac deaths have been widely reported with limited data focused specifically on myocarditis. A retrospective review of cases from the Office of the Chief Medical Examiner (OCME), State of Maryland yielded a total of 103 sudden unexpected deaths (SUDs) due to myocarditis (0.17% of all SUDs and 0.70% of autopsied SUDs) from 2005 through 2014. Most deaths occurred in patients <30 years of age with a male:female ratio 1.3:1. Of the 103 cases, 45 (43.7%) patients were witnessed collapsed. Four deaths occurred during exertion, such as exercising at the gym or performing heavy physical work, and 2 deaths were associated with emotional stress. The common cardiac macroscopic findings included ventricular dilatation (39.8%), mild coronary stenosis (17.5%), mottled myocardial appearance (15.5%), and myocardial fibrosis (10.7%). The histological classification of myocarditis was based on the predominant type of inflammatory cell infiltration. In our study group, lymphocytic myocarditis was most common, accounting for 56 cases (54.4%), followed by neutrophilic (32 cases, 31.7%), eosinophilic (13 cases, 12.6%) and giant cell type (2 cases, 1.9%). Microscopic examination revealed myocyte necrosis in 69 cases (67.0%) and interstitial or perivascular fibrosis in 48 cases (46.6%). The percentage of myocyte necrosis was 75.0% (42/58 cases) in lymphocytic, 65.6% (21/31 cases) in neutrophilic, 30.8% (4/13 cases) in eosinophilic, and 100% (2/2 cases) in giant cell myocarditis. Determination of myocarditis as cause of death continues to present a major challenge to forensic pathologists, because histopathologic findings can be subtle and the diagnosis of myocarditis remains difficult.